Sharing Benefits from Carbon Finance : Lessons from the Guangxi CDM Project - Brodnig, Gernot (World Bank, Washington, DC, 2012)
Carbon finance projects are often intended to be both a payment for an environmental service (PES) and an instrument to facilitate sustainable development in developing countries. To enhance livelihood objectives, these projects should benefit rural land users, provided they are willing and able to participate. This holds particularly true for forest carbon initiatives. However, high transaction costs and large uncertainties often bar local communities from making what are inherently long-term and often expensive investments. Uncertainties arise from ambiguous property rights, vague or rapidly changing government policies and unknown carbon market prices. Additionally, there are risks from human-induced and natural disasters. Since many small-scale poor land users in developing countries have only small plots of land and serious cash-flow or liquidity constraints, they cannot easily absorb negative shocks. Thus, risk acts as a formidable barrier to project participation. Pooling individual activities and signing collective contracts with groups of smallholders spreads both benefits and transaction costs over a large group and can be a practical means for small-scale land users to participate. Nonetheless, pooling requires collective action, the success of which often depends on a mix of property rights, contracts and social capital. These three components are not independent. Contracts operate within a regime of property rights and social capital can determine individuals' ability to enforce contracts through social structures. Thus, to design a successful forest carbon project, we need to understand the important roles played by social capital, property rights and contractual rules in facilitating participation.